Evaluasi Stabilitas Lereng Pada Ruas Jalan C.10 Perumahan Citraland Bandar Lampung Menggunakan Program Komputasi dan Penanggulangannya - Kholiq, Muhammad Nur; Iswan, Iswan; Syah, Aminudin; Zakaria, Ahmad (Universitas Lampung, 2021)
Citraland is a located in a hilly area, has steep contours and different elevations. So the area has the potential for landslides. This study is to analyze the value of the slope safety factor and calculate the slope stability using a concrete sheet pile with a computational program. The methods used are the Fellenius, Bishop, Janbu, and Morgenstern-price methods. From the results of the computational program analysis, the values of the existing slope safety factors using the Fellenius, Bishop, Janbu, and Morgenstern-price methods were 0.965, 1.052, 0.925, 1.027 for static conditions and for dynamic conditions of 0.795, 0.881, 0.763, 0.858 . After countermeasures using concrete sheeting with dimensions of 3 meters of pile height on the ground, 1.66 meters of embedded sheeting, and 0.5 meters of sheet pile thickness, the existing slope safety factor values are 2.381, 2.478, 1.817, 2.732 for static loads and for dynamic loads. obtained values of 1.976, 2.073, 1.505, and 2.356. Countermeasures using concrete sheet piles are quite effective in increasing the value of the safety factor, so that countermeasures using concrete sheet piles are quite stable if applied at the research site. Keywords:Slope stability, Safety factor,Fellenius, Bishop, Janbu,Morgenstern-price, Sheet pile